DISEASE MODIFYING TREATMENT UTILISATION IN MULTIPLE SCLEROSIS. Issue 11 (14th October 2015) - Williams, Owain H; Harding, Katharine E; Willis, Mark; Pickersgill, Trevor; Wardle, Mark; Robertson, Neil P
Abstract : Background: The number of disease modifying treatments (DMT) for multiple sclerosis continues to expand, although there is limited data concerning their long term use and utilisation in clinical practice. Objective: Descriptive analysis of historic and current DMT utilisation in relation to treatment pathways, course length and discontinuation reasons in real practice. Methods: A subset of a population-based cohort of MS identified 270 patients with prospective data on DMT utilisation, reasons for discontinuation were classified. Descriptive and survival analysis were conducted. Results: 498 drug initiation events were identified in 270 patients. 2nd line treatment was initiated in 39%, 3rd line=9%, 4th line=3%, 5th line=0.4%, 6th line=0.4%. Commonest DMT initiated was Interferon (67%) followed by Alemtuzumab, with proportional increase in prescription with each line of treatment escalation (1st=19%, 2nd=26%, 3rd=36%). Persistence on first DMT was a median of 1.7 (1.4–2.3) years for Interferon and 2.7 (0.8–5.1) years for Copaxone, excluding fixed course DMTs. Discontinuation occurred on 307 occasions, with the commonest reason being intolerance of side effects in 57%. Conclusion: The greatest limitation to drug efficacy will be its course length and its appropriate utilisation, thus a greater understanding of drug indication and discontinuation will be of benefit in clinical practice.